Effects of Dance Interventions on Cognition, Psycho-Behavioral Symptoms, Motor Functions, and Quality of Life in Older Adult Patients With Mild Cognitive Impairment: A Meta-Analysis and Systematic Review - Liu, Chang; Su, Mengyu; Jiao, Yuchen; Ji, Yan; Zhu, Shuqin (Frontiers in Aging Neuroscience, 2021)
Background: Dance interventions are considered beneficial for older patients with mild cognitive impairment in many aspects. We conducted a comprehensive systematic review and meta-analysis to assess the effects of dance on different aspects (cognitive function, emotions, physical function, and quality of life) of this population. Methods: A systematic search of PubMed, Web of Science, the Cochrane Central Register of Controlled Trials, Embase, American Psychological Association PsycInfo, ProQuest, Scopus, Cumulative Index to Nursing and Allied Health Literature, the Chinese BioMedical Literature Database, the VIP Database for Chinese Technical Periodicals, China National Knowledge Infrastructure, and Wanfang Data database was performed. Two reviewers independently assessed the study quality. Results: Fourteen studies were retrieved from the databases for analysis. The pooled results showed that dance interventions significantly improved global cognition (standardized mean difference [SMD] = 0.73, 95% confidence interval [CI]: 0.47 to 0.99, P < 0.00001), rote memory (mean difference [MD] = -2.12, 95% CI: –4.02 to –0.21, P = 0.03), immediate recall (SMD = 0.54, 95% CI: 0.30 to 0.78, P < 0.0001), delayed recall (SMD = 0.56, 95% CI: 0.26 to 0.86, P = 0.0002) and attention (SMD = 0.38, 95% CI: 0.13 to 0.64, P = 0.003). No significant improvement was found in executive function, language, depression, anxiety, dementia-related behavioral symptoms, motor function, and quality of life. Conclusion: Dance interventions benefit most aspects of cognitive functions. The evidence for the effects of dance on psycho-behavioral symptoms, motor function and quality of life remains unclear. More trials with rigorous study designs are necessary to provide this evidence.